Number Play Activities as a Strategy to Strengthen Children's Cognitive Readiness to Enter Elementary School - Sunarwati; Ardhana Januar Mahardhani; Siti Fatimah (Journal of Education and Teaching Learning, 2026)
The cognitive readiness of preschool children to enter elementary school remains a problem because some children have difficulty understanding the concept of numbers and number symbols. This study aims to describe the activity of playing numbers using number cards as a strategy to strengthen children's cognitive readiness to enter elementary school at Dharma Wanita 02 Dayakan Kindergarten. This study applies a qualitative approach with a descriptive qualitative research type. The research subjects consisted of 8 children from Group B at Dharma Wanita 02 Dayakan Kindergarten. Data collection methods were carried out through observation, interviews, and documentation, while data analysis included data reduction, data presentation, and drawing conclusions. The study shows that playing numbers with number cards can facilitate children in understanding the concept of numbers, arranging numbers, matching number symbols with the number of objects, and increasing children's participation and enthusiasm during the learning process. Real media and play activities also improve children’s concentration, social interaction and school readiness, social interaction, and children's learning preparation before starting elementary school. Therefore, number cards can be used as an interesting early numeracy learning strategy option that is appropriate to the characteristics of early childhood development.